2016
DOI: 10.1002/art.39504
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Association Study in an Amerindian Ancestry Population Reveals Novel Systemic Lupus Erythematosus Risk Loci and the Role of European Admixture

Abstract: OBJECTIVES Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a strong genetic component. Our aim was to perform the first genome-wide association study on individuals from the Americas enriched for Native American heritage. MATERIALS and METHODS We analyzed 3,710 individuals from four countries of Latin America and the Unites States diagnosed with SLE and healthy controls. Samples were genotyped with the HumanOmni1 BeadChip. Data of out-of-study controls was obtained for the HumanOmni2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(86 citation statements)
references
References 40 publications
1
81
1
2
Order By: Relevance
“…In addition, in the GWAS, several hundred or thousands of markers are removed, particularly by high error rates, including SNPs with an excessive missing genotype . Hence, we cannot discard the possibility that the controversial results found in the present study and those observed in GWAS (which included Mexican patients with SLE) are influenced by the aforementioned aspects . However, it is necessary to carry out additional studies in Mexican patients (and other Latin American populations) with RA or SLE to confirm our findings.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, in the GWAS, several hundred or thousands of markers are removed, particularly by high error rates, including SNPs with an excessive missing genotype . Hence, we cannot discard the possibility that the controversial results found in the present study and those observed in GWAS (which included Mexican patients with SLE) are influenced by the aforementioned aspects . However, it is necessary to carry out additional studies in Mexican patients (and other Latin American populations) with RA or SLE to confirm our findings.…”
Section: Discussionmentioning
confidence: 66%
“…43 Hence, we cannot discard the possibility that the controversial results found in the present study and those observed in GWAS (which included Mexican patients with SLE) are influenced by the aforementioned aspects. 34,35 However, it is necessary to carry out additional studies in Mexican patients (and other Latin American populations) with RA or SLE to confirm our findings. It should be noted that the statistical power of the present study was 92% for RA and 93% for SLE [taking into account the frequency of the VEGFA -1154A allele and the prevalence of RA (1.6%) and SLE (0.06%) in Mexicans].…”
Section: Discussionmentioning
confidence: 67%
“…1,11 Consequently, candidate gene studies and genome-wide association studies (GWAS) have been performed and identified over 70 risk genes associated with SLE that achieve genome-wide significance level (P < 5 9 10 À8 ). [12][13][14][15][16][17][18][19][20][21] Many of these genes participate in known pathways relevant to SLE pathogenesis that are key to innate and adaptive immune responses, lymphocyte activation, and clearance of immune complexes and apoptotic cells. 22 In 2011, a single-nucleotide polymorphism (SNP) rs7704116 in PPP2CA on chromosome 5q31.1 was found to be associated across multi-ancestral SLE cohorts that included Hispanic American, European American and Asian populations (Korea).…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…The heritability of SLE was estimated to be 43·9%, suggesting a strong genetic component to its pathogenesis . Consequently, candidate gene studies and genome‐wide association studies (GWAS) have been performed and identified over 70 risk genes associated with SLE that achieve genome‐wide significance level ( P < 5 × 10 −8 ) . Many of these genes participate in known pathways relevant to SLE pathogenesis that are key to innate and adaptive immune responses, lymphocyte activation, and clearance of immune complexes and apoptotic cells …”
mentioning
confidence: 99%
“…Although the exact etiology of SLE is not fully understood, the familial aggregation of SLE suggests an important contribution of genetics to SLE susceptibility (Kuo et al., ). To date, genome‐wide association studies (GWAS) and candidate gene studies have discovered more than 80 genetic loci with SLE risk that achieve genome‐wide significance ( P < 5 × 10 −8 ) (Alarcon‐Riquelme et al., ; Bentham et al., ; Han et al., ; Langefeld et al., ; Lessard et al., ; Morris et al., ; Sun et al., ; Wen et al., 2017, ). So far, most of the genetic risk loci are shared across borders and ethnicities.…”
Section: Introductionmentioning
confidence: 99%